ANALISIS ANCAMAN DAN MITIGASI SERANGAN CYBER PADA INFRASTRUKTUR INTERNET OF MILITARY THINGS (IOMT) TNI AD : (Kerangka Keamanan Siber Taktis Berbasis Zero Trust) - Agung Prapsetyo; Kiki Lestari; Dorado Sembiring (JURNAL ELEKTROSISTA, 2026)
The development of Internet of Military Things (IoMT) has revolutionized TNI AD's command, control, communications, computers, intelligence, surveillance, and reconnaissance (C4ISR) systems, yet simultaneously expanded significant cyber attack surfaces. This study aims to analyze critical cyber threats to TNI AD's IoMT infrastructure through systematic library research method and develop an adaptive mitigation framework for Disconnected, Intermittent, Limited (DIL) characteristics in tactical networks. Data were collected from 32 primary sources including reputable scientific journals (IEEE, ACM, Elsevier), international standards (NIST, MITRE, NATO), defense policy documents (Kemhan RI, DARPA), and ISBN. Analysis employed Systematic Literature Review (SLR) with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), strengthened by comparative analysis of 15 existing IoT/IoMT security frameworks. Results identified 18 main attack vectors with distribution: perception layer (44%), network layer (33%), and application layer (22%). The proposed mitigation framework integrates Zero Trust Architecture (ZTA), lightweight cryptography (ASCON, Grain-128AEAD), and edge-based anomaly detection with 91-96% detection efficiency based on meta-analysis of empirical studies. The scholarly contribution lies in ZTA adaptation for tactical edge computing aligned with TNI AD operational doctrine and DIL constraints.